La polysémie et le réseau synonymique des prédicats polylexicaux - Meneses, Luis (Neophilologica, 2011)
Our objective is to deal with the question of polysemy and synonymy of fixed verbal sequences from the perspective of the three primary functions. Assuming that the elementary phrase is a minimal unit of analysis, the verb to give, which is a focal point of our study, can function as a predicate of the phrase, an actualizer of a nominal predicate or an element of a fixed sequence. The notion of usage will help us to demonstrate that the meaning of some verbal phrases changes according to their phrasal context, which shows that polysemy is not exclusive to mono-lexical units. Moreover, the representation of the different meanings of a multi-lexical unit is expressed by a vast synonymy and paraphrase network. The current study is in line with an Automatic Language Processing perspective that aims for recognition fixed sequences, for the generation of automatic phrases and for automatic translation. We shall present, firstly, our methodological framework. Secondly, we shall focus on the polysemy of multi-lexical predicates to demonstrate the characteristics they share and the differences between them and mono-lexical predicates. Finally, we shall put forward a methodology of treating the polysemy and synonymy of fixed sequences.